Kinetic study on martensite formation in steels 1045 and 4340 under variable cooling rates - Bubnoff, Dimitry V (2018)
The experiments were carried with two steels with different chemical compositions, aiming at understanding and comparison with the available literature. The microstructures of steels 1045 and 4340 were characterized and quantified using scanning electron microscopy (SEM) and optic microscopy (OM) with quantitative methods. Based on the experimental results, the amount of martensite, the hardness and the microhardness were determined, as a function of the distance from the quenching end, under different cooling conditions. For predicting the evolution of martensitic fraction along the sample, Koistinen-Marburger’s (K-M) model was adopted. It was found  that the parameters recommended in the literature for the traditional K-M model do not represent accurately the results obtained for the steel samples under investigation. According to indications found in recent literature, parameter corrections were proposed, leading to a modified K-M model which better represents the transformations observed in the different examined steels.